La inversión en las Fintech y su influencia en la percepción de la rentabilidad de los usuarios del sector bancario de Lima Metropolitana en el año 2022 - Bravo Fernández, Sandra Carolina (2023)
The present study aims to demonstrate that investments in non-traditional companies, such as Fintech’s, generate a higher return than the financial products offered by the traditional banking institutions in the country. Additionally, the research highlights the importance of these new players within the financial system due to the existence of an oligopoly of banking entities that do not offer competitive savings rates to users. Initially, a literature review was conducted to gather information available to date regarding the variables considered in this study, thereby demonstrating that both nationally and internationally, these companies are in a consolidation process with significant growth potential. According to Vodanovic Legal magazine, in Peru, the creation of these companies has increased by 15% compared to 2021, thereby promoting financial inclusion. (Vodanovic Legal, 2022) Subsequently, a survey was administered to users in the banking sector in Lima to gather insights into their experiences with traditional banking and its channels. The majority of respondents were young adults between the ages of 18 and 35, who expressed strong approval of the digitalization of banking services due to valuing the speed of their use; however, only a few individuals were aware of the existence of these companies. In conclusion, we find that this sector is still relatively unknown to the population, and there is a need to develop communication and marketing strategies to attract potential clients. Many of whom would be willing to utilize these services, but their lack of knowledge and limited exposure raises doubts about their reliability.